A Location Prediction Algorithm with Daily Routines in Location-Based Participatory Sensing Systems. (18th October 2015) - Yu, Ruiyun; Xia, Xingyou; Liao, Shiyang; Wang, Xingwei
Mobile node location predication is critical to efficient data acquisition and message forwarding in participatory sensing systems. This paper proposes a social-relationship-based mobile node location prediction algorithm using daily routines (SMLPR). The SMLPR algorithm models application scenarios based on geographic locations and extracts social relationships of mobile nodes from nodes' mobility. After considering the dynamism of users' behavior resulting from their daily routines, the SMLPR algorithm preliminarily predicts node's mobility based on the hidden Markov model in different daily periods of time and then amends the prediction results using location information of other nodes which have strong relationship with the node. Finally, the UCSD WTD dataset are exploited for simulations. Simulation results show that SMLPR acquires higher prediction accuracy than proposals based on the Markov model.